Physicians’ Perception on Allergic Rhinitis and Its Management: A Questionnaire Based Survey - Prabhat, Divya (Indian J Otolaryngol Head Neck Surg, 2018)
Despite high prevalence and impact on quality of life, Allergic Rhinitis (AR) is undertreated. Furthermore, existence of a relationship between AR and upper respiratory tract infection (URTI) is less explored. This Pan-India survey intended to assess physicians’ perception about AR and URTI, and management practices in Indian setting. This questionnaire-based survey was conducted by telephonically interviewing 300 physicians [Consultant Physicians (CP): 33%; General Physicians (GP): 32%; ENT surgeons: 16%; pediatricians: 11%; allergy specialists: 8%] across India. CPs (33%) and GPs (32%) treated more AR patients in a month, versus other specialties. According to physicians, about 29.6% of patients with AR develop URTI in a month. Majority of the physicians (98%) believed that recurrent URTI can be considered as an indicator of undiagnosed AR. Majority of the physicians (98%) also considered AR to be a predisposing factor for increased risk of URTI. About 62% agreed that prompt diagnosis and treatment of AR can reduce the risk of complications such as URTI. Most preferred first- and second-line of treatment (alone or in combination) in AR management were oral antihistamines (41%) and intranasal corticosteroids (40%), respectively. Similar treatment preferences were observed irrespective of physicians’ specialization and years of experience. This survey sheds light on the need to implement clear guidelines for the diagnosis and management of AR.